Indigenous knowledge representation in mitigation process: a study of communities' understandings of natural disasters in Aceh Province, Indonesia. (6th November 2018) - Syahputra, Hendra
Abstract : Purpose: The purpose of this paper is to explore the case studies of communities' understandings of natural disasters in Aceh Province, Indonesia, where a number of cultures and traditions which belong to the ancestral heritage continue to be used in a more modern context. Design/methodology/approach: This research used a qualitative descriptive research paradigm in which the researcher attempted to describe or construct in-depth interview results for the research objects. The interviews were conducted in six disaster-prone areas in Aceh, i.e. Simeulue, Central Aceh, Aceh Tamiang, Pidie Jaya, North Aceh and dan Pidie. The interviewees were the informants in this research, which included traditional leaders, religious leaders, community leaders, headmen, youth figures and disaster victims. The technique for determining informants was through purposive sampling in which the sample is specified based on the need of the research. Findings: Majority of the people in Aceh, especially those who live in earthquake- and tsunami-prone areas still practice this form of knowledge, as they have already realized that it makes a significant contribution to emergency management. They typically used their traditional knowledge to understand both the nature of local hazards and the risk reduction mechanism related to response mechanisms. In some events, they also used it as an alternative to recovery phase according to past information and experiences. This paper will discuss the contribution of traditional knowledge to emergency management by presenting some specific cases of indigenous stories in Aceh. The stories not only served as an early warning system but also can be used to develop more effective disaster risk reduction programmes to improve community awareness to deal with future threats. Originality/value: On Simeulue Island, most of the indigenous people already possess the knowledge and value systems inherited through the generations, as a form of local wisdom "called smong " when encountering earthquakes and tsunamis. Beside smong, there is still considerable amount of other similar indigenous knowledge that originated amid traditional people, especially in rural areas, in Aceh. Thus, this paper attempts to identify the knowledge and its representation in the implementation of disaster mitigation efforts in Aceh.